Exploring and Addressing Factors Contributing to Reading Proficiency Differences: Teachers’ Perspectives (Journal of NELTA, 2024)
Proficient reading is fundamental to succeed in all academic success. However, there are significant reading proficiency differences among secondary level students in Nepal. This article identifies a multitude of factors contributing to reading proficiency differences and teacher strategies in the classroom to mitigate these differences. By using a qualitative case study design, two secondary level English teachers in Kathmandu were interviewed to explore their experiences with students who exhibit varied reading profiles. Thematic analysis of data revealed three categories of factors influencing reading proficiency differences among students: reader factors, home literacy environment, and text factors. Moreover, teachers employed a number of strategies to address reading disparities among students. These strategies include: differentiated instruction, explicit instruction, fostering motivation and interest, creating a learning environment, building background knowledge, addressing anxiety, and promoting self-efficacy.